Analysis Of Workload On Employees In The United Nations And Political Agency (BAKESBANGPOL) - Yobellika Br Depari; Budi Rismayadi; Wike Pertiwi (PT. Berkah Digital Teknologi, 2024)
Purpose of the study - The purpose of this study is to analyze workloads on employees at the Karawang Regency National and Political Unity Agency (BAKESBANGPOL) and determine whether the workload suits the number of employees. This research aims to address the problem of employee workload at BAKESBANGPOL Karawang Regency. Research method- This study uses a qualitative approach with data collection techniques using interviews. The sample consisted of 16 people. The data analysis methods used descriptive analysis. Result- The results showed that employee workload at BAKESBANGPOL was very high due to an imbalance between the number of employees and workload. This has a negative impact on work efficiency and employee welfare. Conclusion- It can be concluded that the workload analysis conducted is important to evaluate workload balance and optimize working time. There is a need to increase human resources to ensure operational efficiency. This research can be used as a basis for improving human resource management and increasing work efficiency at BAKESBANGPOL Karawang Regency.